Decreased Empathic Responses to the ‘Lucky Guy’ in Love: The Effect of Intrasexual Competition - Zheng, Li; Zhang, Fangxiao; Wei, Chunli; Xu, Jialin; Wang, Qianfeng; Zhu, Lei; Roberts, Ian D.; Guo, Xiuyan (Frontiers in Psychology, 2016)
People have a greater desire to date highly attractive partners, which induces intrasexual competition between same-sex individuals. The present study used functional magnetic resonance imaging to explore whether and how intrasexual competition modulates pain empathy for a same-sex rival and the underlying neural mechanism. Participants were scanned while processing the pain of a same-sex ‘lucky guy’ who had an attractive partner and one with a plain partner. The results revealed that participants reported lower pain intensity for the lucky guy. Neurally, reduced pain-related activations in anterior insula and anterior mid-cingulate cortex and increased activations in right superior frontal gyrus (SFG) and medial prefrontal gyrus (MPFC) were found for the lucky guy compared to the one with a plain partner. Right SFG and MPFC activations could predict participants’ subsequent pain intensity ratings for the lucky guy. These findings suggest intrasexual competition can modulate normal empathic responses.